The Conductor As Visual Guide: Gesture and Perception of Musical Content - Kumar, Anita B.; Morrison, Steven J. (Frontiers in Psychology, 2016)
Ensemble conductors are often described as embodying the music. Researchers have determined that expressive gestures affect viewers’ perceptions of conducted ensemble performances. This effect may be due, in part, to conductor gesture delineating and amplifying specific expressive aspects of music performances. The purpose of the present study was to determine if conductor gesture affected observers’ focus of attention to contrasting aspects of ensemble performances. Audio recordings of two different music excerpts featuring two-part counterpoint (an ostinato paired with a lyric melody, and long chord tones paired with rhythmic interjections) were paired with video of two conductors. Each conductor used gesture appropriate to one or the other musical element (e.g., connected and flowing or detached and crisp) for a total of sixteen videos. Musician participants evaluated 8 of the excerpts for Articulation, Rhythm, Style, and Phrasing using four 10-point differential scales anchored by descriptive terms (e.g., disconnected to connected, and angular to flowing.) Results indicated a relationship between gesture and listeners’ evaluations of musical content. Listeners appear to be sensitive to the manner in which a conductor’s gesture delineates musical lines, particularly as an indication of overall articulation and style. This effect was observed for the lyric melody and ostinato excerpt, but not for the chords and interjections excerpt. Therefore, this effect appears to be mitigated by the congruence of gesture to preconceptions of the importance of melodic over rhythmic material, of certain instrument timbres over others, and of length between onsets of active material. These results add to a body of literature that supports the importance of the visual component in the multimodal experience of music performance.